Infantry combat the theory and practice of infantry warfare 1914-2000 - Wiest, Andrew A.; Barbier, M. K. (Amber Books, 2017)
From the trenches of the Somme to the ruins of Stalingrad to the deserts of Iraq, the role of the infantry soldier developed dramatically throughout the twentieth century. Infantry Combat examines the changing roles that took place for infantry from 1900 to the year 2000. With the introduction of tanks during World War I, infantry were no longer the shock arm in battle but became responsible for securing objectives that tanks had taken. But this wasn't to be the case all around the world, as in areas inaccessible to tanks, such as the jungles of the Pacific islands or Vietnam, the infantry were once again the primary means of waging war. And while the Cold War and nuclear weapons threatened to reduce the infantry to a secondary role, the increase in limited operations, often against less well-equipped opponents, saw the common soldier once again in the forefront. And what future the combat soldier? The book concludes with an examination of robotics and new mechanisation on the battlefield. Illustrated with action photographs and battle maps, Infantry Combat uses examples from an immense range of twentieth century combat situations to provide a definitive guide to modern infantry warfare.